Penyuluhan dalam Rangka Peningkatan Pengetahuan Manajemen Pakan Ayam Petelur di Indramayu - Novi Mayasari; Laela Tien Nurjanah (Universitas Serang Raya, 2020)
Feed management is one aspect in the livestock business that must be considered because it includes factors that affect production costs. The Farmers Group in Indramayu received a grant from one of the State-Owned Enterprises (BUMN) to develop the laying hens business. Based on the survey that has been done, the problem faced by this breeders group is the lack of insight about good feed management. These problems will indirectly affect the sustainability of the business being run. Therefore there is a need for counseling to increase the knowledge of breeders' groups regarding feed management in order to maintain and improve the sustainability of the business being run. Counseling activities carried out by lecture method and interspersed with discussions based on information that has been presented. Before and after counseling activities are evaluated (Pre-test and Post-test). Based on the evaluation conducted, it can be concluded that there was a significant increase in knowledge after the training activities, as evidenced from the questionnaire level of knowledge of farmers at the time before counseling only 20% to 100% after counseling. Furthermore, it is necessary to assist farmers in the application directly to the application of material that has been given during counseling, so that business continuity is getting better and increasing.